A multi-dimensional framework for responsible and socially inclusive digital innovation in food, water, and land systems - Opola, Felix Ouko; Langan, Simon; Arulingam, Indika; Schumann, C.; Singaraju, N.; Joshi, Deepa; Ghosh, Surajit (Springer, 2025)
Digital innovations can offer solutions to various food, water, and land systems challenges globally. However, there are concerns on the ethical and social inclusivity aspects of these innovations, particularly for marginalized groups of people in less industrialised countries. In this article, we describe the design and development of a digital inclusivity framework, which builds from a detailed synthesis of inclusivity in digital literature. Key insights from the review were collated into five dimensions: risk mitigation, accessibility, usability, benefits, and participation. These dimensions can be assessed by means of twenty-one concrete and measurable sub indicators. Our focus was to enable a more holistic approach to the usually technocentric design of digital innovations. The framework, including the associated indicators, lays the groundwork for the development of a digital inclusivity index, a tool for assessing and fostering the inclusivity of digital innovations in food, water, and land systems.